Novel Zinc and Vanadium (V) Hydroquinonate Complexes: Synthesis and Biological Solution Evaluation - Ioannou, Kyriakos; Eleftheriou, Constantina; Drouza, Chryssoula; Pafiti, Kyriaki S.; Panayi, Tolis; Keramidas, Anastasios D.; Zacharia, Lefteris C.; Vlasiou, Manos C. (My University, 2022)
Four novel mononuclear complexes of Zn2+ and V5+ ions were synthesized by the chelation of tridentate ligands of hydroquinone derivatives in 1:1 M ratios. The synthesis of the two novel ligands and their metal complexes were identified and characterized by NMR, IR, UV–Vis, cyclic voltammetry, and conductivity measurements. Structural information was also collected using computational chemistry and density functional theory studies. The biological activity of these metal complexes was investigated by the ctDNA interaction process via UV–Vis and viscosity measurements. The synthesized compounds C1 – C4 were primarily screened for their in vitro anti-microbial activities against gram-positive, gram-negative bacteria, and their anticancer potential against MDA-MB-231 cells carried out by MTT assay. Furthermore, on the complex molecules, we performed DPPH antioxidant studies and BSA (bovine serum albumin) binding studies on the UV–Vis. Additionally, studies were performed in silico by molecular docking evaluation of the molecules against breast cancer-related proteins. The data show that complexes C1- C4, have anticancer activity even in cells that showed resistivity against cis-platin (C3 > C4 > C2, C1) and the complexes (C2 > C1), have antibacterial activity against gram-positive bacteria. Another remarkable piece of evidence is that the anticancer activity of the molecules does not occur only because of their prooxidant activity, since C4 compound resulted in antioxidant activity.
Keywords: Antibacterial; Anticancer; Metal complexes; Synthesis; Vanadium; Zinc